Simulation Development Content for Students Employability in Logistics and Transportation Field in Malaysia - Nizamuddin Zainuddin; Adam Mohd Saifudin; Ahmad Yusni Bahaudin; Mohd Hanizan Zalazilah; Roslan Jamaluddin (International Journal of Supply Chain Management, 2016)
As educational technology has improved, the effective use of simulations has greatly increased to the point where simulations should be considered a valuable, mainstream pedagogical tool. Simulations, in concert with other experiential teaching tools, allow lecturers to facilitate learning more effectively. Simulation is all about representing the real world which includes grasping the complex issues and solving intricate problems and it affects students employability rate in a way of preparing the students base on the market needs. This paper will looked into simulation content development which is all about developing, enriching and the applications of internet protocols in order to enrich the work-related competencies experience among graduate in the field of logistics and transportations and will focus on the real challenges inputs to the generic workflow of the simulation content development. The study was carried out within multi-national and local manufacturing companies, third party companies (3PL) and government agency which are selected from Peninsular Malaysia. A qualitative approach was mainly conducted to gather data in the study. It was then discovered from the study that the systems used in process of outbound and inbound are System Application Products (SAP) and Material Requirement Planning (MRP). It was further discovered that there are only four companies using Enterprises Resources Planning (ERP) and Electronic Data Interchange (EDI) as part of the Suppliers Own Inventories (SOI) networking as a result of globalized business between one country to another. It was further shown that the resources involved in the outbound and inbound processes are computerized documentation i.e. email, telephones and fax well trained staff handling the processes in computer system and dealing with suppliers and customers. The study contributes to the body of knowledge on the enrichment of the students employability. It also provided practical recommendations in the area of training for the organizations and curriculum adapting and development for the universities.